Exposure-response analysis of risk of respiratory disease associated with occupational exposure to chrysotile asbestos. Issue 9 (September 1997) - Stayner, L; Smith, R; Bailer, J; Gilbert, S; Steenland, K; Dement, J; Brown, D; Lemen, R
Abstract : OBJECTIVES: To evaluate alternative models and estimate risk of mortality from lung cancer and asbestosis after occupational exposure to chrysotile asbestos. METHODS: Data were used from a recent update of a cohort mortality study of workers in a South Carolina textile factory. Alternative exposure-response models were evaluated with Poisson regression. A model designed to evaluate evidence of a threshold response was also fitted. Lifetime risks of lung cancer and asbestosis were estimated with an actuarial approach that accounts for competing causes of death. RESULTS: A highly significant exposure-response relation was found for both lung cancer and asbestosis. The exposure-response relation for lung cancer seemed to be linear on a multiplicative scale, which is consistent with previous analyses of lung cancer and exposure to asbestos. In contrast, the exposure-response relation for asbestosis seemed to be nonlinear on a multiplicative scale in this analysis. There was no significant evidence for a threshold in models of either the lung cancer or asbestosis. The excess lifetime risk for white men exposed for 45 years at the recently revised OSHA standard of 0.1 fibre/ml was predicted to be about 5/1000 for lung cancer, and 2/1000 for asbestosis. CONCLUSIONS: This study confirms the findings from previous investigations of a strong exposure-response relation between exposure to chrysotile asbestos and mortality from lung cancer, and asbestosis. The risk estimates for lung cancer derived from this analysis are higher than those derived from other populations exposed to chrysotile asbestos. Possible reasons for this discrepancy are discussed.